Proceso administrativo. Financiero y su incidencia en el rendimiento económico de las distribuidoras de insumos agropecuarios del cantón Buena Fe año 2012, anual operacional. - Cabrera Casanova, Daniela (2013)
This research was development evaluation of the administrative process leading from the central agricultural Canton Good Faith, as a necessary tool to plan, organize and control all administrative aspects for the benefit of their owners. The main objective of this research was to determine if these agricultural companies in the central area of Canton Good Faith, in the province of Los Ríos had administrative tools needed to strengthen business and know the financial impact would generate adequate management within the context social and employment. It is important for owners of agricultural core zone of the canton Good Faith, have easy to use tools that allow integrated sustainable development and sustainable over time, within the framework of administrative development. It was derived from the main agricultural center area of the canton Good Faith, the information was collected through surveys and interviews with owners, managers, warehouse managers, and administrative staff based on a structured questionnaire, which allowed reaching desired target. Were determined strengths, opportunities, threats and weaknesses that the administration has studied agricultural to pose an administrative organizational design that allows proper development favoring the company with an economic flow better off contributing to the satisfaction of the owners.